Observation of both debye type and Maxwell-Wagner relaxation in Y 1.9 Ce 0.1 CoMnO 6 - Anand K.; Pal A.; Alam M.; Mohan A.; Chatterjee S. (My University, 2025)
The dielectric and resistivity measurement have been observed for polycrystalline sample of double pervoskite Y 1.9 Ce 0.1 CoMnO 6. Dielectric constant shows Maxwell-Wagner and Debye both type of mechanism. Semiconducting nature of resistivity has been observed for present sample. © 2019 Author(s).